Functional outcome of the sinus tarsi approach in the treatment of intraarticular calcaneal fractures - Gadhavi, Raj N.; Gohil, Soham B. (International Journal of Research in Orthopaedics, 2025)
Background: Intraarticular calcaneal fracture is reported as an acceptable less traumatic and reproducible procedure by several authors. We have evaluated the clinical, radiological, and functional outcome of such fractures in thirty patients, all of which were managed by sinus tarsi approach an average follow-up period of 18 months. Though open reduction is prevailing, this technique also gives favorable outcome. Methods: Thirty patients with intraarticular calcaneal fracture were managed by dorsal tarsi approach using between March 2023 to November 2025 were included in this series. All cases were treated with closed reduction. The dominant side, gender ratio, surgery time, and fracture union time, and complications were noted. Results: Of the Thirty patients in the study, twenty-two were males and eight were females. The mean age was 40.4 years (range 18 to 65 years). Eighteen out of thirty patients (60%) had the dominant side fractured). The mean fracture union (radiological) time was 8 weeks (range: 6-12 weeks) and clinical union time was 8.5 weeks week. However, ankle function was excellent in 30 cases (100%). Conclusions: This study confirmed a high overall rate of union and excellent functional outcomes sinus tarsi approach for a intraarticular calcaneal fractures give good functional results and should be considered as an effective, cosmetically advanced surgical option in the treatment of type A humeral shaft fractures. It is a safe and less time-consuming method intraarticular calcaneal fracture. When the surgeon is experienced in the technique.